How Mg2+ ions lower the SN2@P barrier in enzymatic triphosphate hydrolysis. Issue 28 (14th March 2018) - van Bochove, Marc A.; Roos, Goedele; Fonseca Guerra, Célia; Hamlin, Trevor A.; Bickelhaupt, F. Matthias
Abstract : Our activation strain analyses highlight the key role of Mg 2+ ions during enzymatic triphosphate hydrolysis associated with DNA replication. Abstract : Our quantum chemical activation strain analyses demonstrate how Mg 2+ lowers the barrier of the enzymatic triphosphate hydrolysis through two distinct mechanisms: (a) weakening of the leaving-group bond, thereby decreasing activation strain; and (b) transition state (TS) stabilization through enhanced electrophilicity of the triphosphate PPP substrate, thereby strengthening the interaction with the nucleophile.